Presidents’ Messages – Honouring the past, embracing the future - Vandale, Tanya; Hahn, Bryana (Operating Room Nurses Association of Canada Journal, 2026)
A Message from the Outgoing President Serving as president of ORNAC over the past three years has truly been a journey — one grounded in learning, adapting, mentorship, and lasting friendships. It has been both an honour and a humbling experience to lead this national professional organization during a time of change. A Message from the Incoming President It is with great respect and enthusiasm that I step into the role of president of ORNAC. I would like to begin by expressing my sincere appreciation to our outgoing president for her exceptional leadership, dedication, and vision over the past three years. Her commitment has helped guide ORNAC through meaningful transformation and has strengthened the organization for the future.